Vancomycin susceptibility trends of methicillin-resistant Staphylococcus aureus isolated from burn wounds: a time for action - Abdulaziz Abdulhafid Zorgani; Omar Elahmer; Ahmed Abaid; Ahlam Elaref; Samira Elamri; Eziddin Aghila; Abdullatif Tubbal (Journal of Infection in Developing Countries)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) with reduced susceptibility to vancomycin poses a threat for patients in burn units throughout the world. This study aimed to investigate the reduced susceptibility to vancomycin of MRSA isolated from wounds of patients admitted to the Burns and Plastic Surgery Centre in Tripoli, Libya. Methodology: All isolates were initially identified by chromagen medium then confirmed by PCR. The minimum inhibition concentration (MIC) was determined by E-test glycopeptide resistance detection (GRD). Results: During the study, 210 isolates were obtained from 560 patients representing 132 (62.9%) and 78 (37.1%) of total samples received during years 2009 and 2010, respectively. MIC levels for vancomycin ranged from 0.5 to 2 µg/ml during the study, 13% of isolates displayed MIC of 1.5 µg/ml and 9% of the isolates displayed 2 µg/ml. Although MRSA isolates decreased dramatically during 2010 (37.1%) compared to 2009 (62.9%), overall, there was a significant increase in the proportion of MRSA isolates exhibiting higher vancomycin MICs during 2010 compared to 2009 (P= 0.0155). There was a significant increase of MICs at 1 µg/ml during 2010 compared with 2009 (P = 0.36). No vancomycin intermediate or resistant strains were found. Conclusion: There was a significant increase in the proportion of MRSA isolates exhibiting higher vancomycin MICs. We recommend that MRSA isolates should be monitored. Furthermore, implementation of infection control measures is urgently needed to prevent the spread of MRSA.